Gathering storm: an introduction to the special issue on climate change and terrorism - Silke, Andrew; Morrison, John (Taylor & Francis, 2022)
Climate change is a potential major driver of future terrorism. It is already recognised by many (if not most) nations as a strategic security threat, though the potential role it can play in igniting, facilitating, or exacerbating terrorist conflict has been relatively unexplored. There are, however, growing signs that climate change—either through direct or indirect impacts—should be considered as a significant macro-level driver of terrorism.
Special Issue on Climate Change and Terrorism